Dinamika Kekerasan dalam Hubungan Romantis dan Interpersonal Trust pada Dewasa Awal di Indonesia - Lourdes Clayrence; Naomi Soetikno (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
Early adulthood is a crucial developmental phase characterized by the search for self-identity, the need for emotional intimacy, and the development of maturity in interpersonal relationships. However, this process is often accompanied by relational dynamics that are not always adaptive, including the occurrence of intimate partner violence (IPV) in romantic relationships. This study aims to analyse the relationship between IPV and interpersonal trust in early adult individuals in Indonesia. The study uses a correlational quantitative design involving 347 participants aged 20–40 who have a history of either giving or receiving dating violence. The research instruments used were the IPV scale and Interpersonal Trust scale, both showing high reliability (α = 0.920 and α = 0.932). As the data were not normally distributed (p < 0.001), the analysis was conducted using Spearman correlation. The results showed a significant positive correlation between IPV and interpersonal trust (Rs = 0.254, p < 0.001).  These findings contradict the general theory and previous research results, which tend to show a negative relationship, thereby providing new insights into the characteristics of interpersonal trust in the context of romantic relationships in Indonesia.